Sol–gel synthesis and characterization of ysz nanofillers for dental cements at different temperatures - Beketova, Anastasia; Theocharidou, Anna; Tsamesidis, Ioannis; Rigos, Athanasios E.; Pouroutzidou, Georgia K.; Tzanakakis, Emmanouil George C.; Kourtidou, Dimitra; Liverani, Liliana; Arango Ospina, Marcela; Anastasiou, Antonios; Tzoutzas, Ioannis G.; Kontonasaki, Eleana (Dentistry Journal, 2021)
Background: Yttria-stabilized zirconia nanoparticles can be applied as fillers to improve the mechanical and antibacterial properties of luting cement. The aim of this study was to synthesize yttria-stabilized zirconia nanoparticles by the sol–gel method and to investigate their composition, structure, morphology and biological properties. Methods: Nanopowders of ZrO2 7 wt% Y2O3 (nY-ZrO) were synthesized by the sol–gel method and were sintered at three different tempera-tures: 800, 1000 and 1200◦C, and their composition, size and morphology were investigated. The biocompatibility was investigated with human gingival fibroblasts (hGFs), while reactive oxygen species (ROS) production was evaluated through fluorescence analysis. Results: All synthesized materials were composed of tetragonal zirconia, while nanopowders sintered at 800◦C and 1000◦C additionally contained 5 and 20 wt% of the cubic phase. By increasing the calcination temperature, the crystalline size of the nanoparticles increased from 12.1 nm for nY-ZrO800 to 47.2 nm for nY-ZrO1200. Nano-sized particles with good dispersion and low agglomeration were received. Cell culture studies with human gingival fibroblasts verified the nanopowders’ biocompatibility and their ROS scavenging activity. Conclusions: the obtained sol–gel derived nanopowders showed suitable properties to be potentially used as nanofillers for dental luting cement.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Chemical precipitation; Gingival fibroblasts; Nanoparticle; Oxidative stress; Toxicity tests; Yttrium; Zirconium